1, 3, 2‐Diazaphospholenes Catalyze the Conjugate Reduction of Substituted Acrylic Acids. Issue 17 (8th July 2020) - Reed, John H.; Cramer, Nicolai
Abstract: The potent nucleophilicity and remarkably low basicity of 1, 3, 2‐diazaphospholenes (DAPs) is exploited in a catalytic, metal‐free 1, 4‐reduction of free α, β‐unsaturated carboxylic acids. Notably, the reduction occurs without a prior deprotonation of the carboxylic acid moiety and hence does not consume an additional hydride equivalent. This highlights the excellent nucleophilic character and low basicity of DAP‐hydrides. Functional groups such as Cbz group or alkyl halides which can be problematic with classical transition‐metal catalysts are well tolerated in the DAP‐catalyzed process. Moreover, the transformation is characterized by a low catalyst loading, mild reaction conditions at ambient temperature as well as fast reaction times and high yields. The proof‐of‐principle for a catalytic enantioselective version is described. Abstract : Potent nucleophilicity yet low basicity : A 1, 3, 2‐diazaphospholene (DAP) catalyst in conjunction with PhSiH3 enables the direct conjugate reduction of substituted α, β‐unsaturated carboxylic acids without prior deprotonation, highlighting its remarkably potent nucleophilicity and yet low basicity. The transformation is characterized by a low catalyst loading, mild reaction conditions at ambient temperature as well as fast reaction times and tolerates functional groups such as Cbz group or alkyl halides that can be problematic with classical reduction catalysts.